PharmML in Action: an Interoperable Language for Modeling and Simulation. (15th September 2017) - Bizzotto, R; Comets, E; Smith, G; Yvon, F; Kristensen, NR; Swat, MJ
Abstract : PharmML1 is an XML‐based exchange format2 3 4 created with a focus on nonlinear mixed‐effect (NLME) models used in pharmacometrics, 5 6 but providing a very general framework that also allows describing mathematical and statistical models such as single‐subject or nonlinear and multivariate regression models. This tutorial provides an overview of the structure of this language, brief suggestions on how to work with it, and use cases demonstrating its power and flexibility.